Managing Bottom up Strategizing: Collective Sensemaking of Strategic Issues in a Dutch Bank. Issue 6 (December 2017) - van der Steen, Martijn
Abstract : This paper discusses a bottom-up approach to strategizing in two member banks of a Dutch cooperative bank. In both banks, through a collective process of sensemaking, organisational participants evaluated their day-to-day experiences in order to identify strategic issues. The potential benefits of such approach include higher commitment for strategy and a greater willingness to change. However, the sensemaking occasions in the two banks were organised quite differently. In one bank they were highly structured, whilst the other bank employed a more laissez-faire approach. These two different types of sensemaking resulted in very different outcomes. A single and widely supported strategic issue was identified in one bank. In the other bank, the identification of several conflicting issues made a variety of tacit tensions apparent and available for potential resolution. The paper thus highlights how the design and the management of sensemaking occasions can produce rather distinct outcomes which may be more or less suited to the original managerial intentions.